2012
DOI: 10.9790/0853-0251620
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Alcohol Consumption Modulates the Clotting Time In Wistar Rats

Abstract: Abstract:The study investigated the changes in blood clotting time due to the effect of chronic consumption of alcohol. Thirty six (36) adult male Wistar rats were randomly divided into six groups of A, B, C, D, E and F (n=6)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Moreover, a deformed structure is likely promoted by increased salt intake, which likely increases reactive oxygen species (ROS) in male hamster renal medulla cells and viable horse sperm (Burnaugh, 2010). It has been also reported that high salt dose leads to testicular distortions in wistar rats because salt intake impacts the male reproductive system negatively (Nwangwa, 2015). Distortion of the testicular architecture caused by severe degeneration of testicular tissues, spermatogenic arrest, and focal area of hemorrhage was noticed in the photomicrograph of group 3 testicular section which ingested Mmahi salt for four weeks, followed by 2 weeks of self-recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a deformed structure is likely promoted by increased salt intake, which likely increases reactive oxygen species (ROS) in male hamster renal medulla cells and viable horse sperm (Burnaugh, 2010). It has been also reported that high salt dose leads to testicular distortions in wistar rats because salt intake impacts the male reproductive system negatively (Nwangwa, 2015). Distortion of the testicular architecture caused by severe degeneration of testicular tissues, spermatogenic arrest, and focal area of hemorrhage was noticed in the photomicrograph of group 3 testicular section which ingested Mmahi salt for four weeks, followed by 2 weeks of self-recovery.…”
Section: Discussionmentioning
confidence: 99%